Predictive factors for liver volume and function recovery after resection using three-dimensional analysis. Issue 6 (June 2020) - Nakano, Yutaka; Itano, Osamu; Shinoda, Masahiro; Kitago, Minoru; Yagi, Hiroshi; Abe, Yuta; Takeuchi, Ayano; Takemura, Yusuke; Kitagawa, Yuko
Abstract: Background: Clinical and biological factors that predict liver volume recovery rate (LVRR) after liver resection of different resected volume (RV) have not been studied extensively. Moreover, it remains uncertain whether remnant liver volume influences the liver function recovery rate (LFRR). This study examined the predictive factors for LVRR after liver resections of different RV and investigated LFRR by focusing on LVRR improvements after hepatectomy. Methods: Patients who underwent hepatectomy between January 2013 and August 2015 were reviewed retrospectively. LVRR and LFRR were assessed at postoperative months (POMs) 3, 6, and 12. LVRR was evaluated on the basis of RV (0%–15%, 15%–30%, 30%–45%, and >45%). LFRR was evaluated using total bilirubin, prothrombin time, and platelet count. Results: LVRR was lower with more extensive liver resections. Significant independent predictors of LVRR were type IV collagen 7s domain levels and resection magnitude. Platelet count correlated positively with LVRR at all POMs. Conclusions: Resected livers regenerated after surgery but did not reach preoperative volumes. Preserving the liver as much as possible during resection can result in greater LFRR after hepatectomy. Therefore, decisions regarding liver resection volume should be made very carefully, particularly in patients with higher type IV collagen 7s domain levels.